IT service management: towards a contingency theory of performance measurement - Gacenga, F.; Cater-Steel, A.; Tan, Wui-Gee; Toleman, M. (ICIS, 2011)
Information Technology Service Management (ITSM) focuses on IT service creation, design, delivery and maintenance. Measurement is one of the basic underlying elements of service science and this paper contributes to service science by focussing on the selection of performance metrics for ITSM. Contingency theory is used to provide a theoretical foundation for the study. Content analysis of interviews of ITSM managers at six organisations revealed that selection of metrics is influenced by a discrete set of factors. Three categories of factors were identified: external environment, parent organisation and IS organisation. For individual cases, selection of metrics was contingent on factors such as organisation culture, management philosophy and perspectives, legislation, industry sector, and customers, although a common set of four factors influenced selection of metrics across all organisations. A strong link was identified between the use of a corporate performance framework and clearly articulated ITSM metrics.